Insights and Advancements in Microfluidics - Hengdong Xi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Microfluidics has developed rapidly over the past three decades. Relentless diagnostic, medical and chemical applications have been demonstrated in various applications, plateforms and tools. Have microfluidics realized its full potential? Or is it only a leveraging academic tool? In this Special Issue, we focus on both insights and advancements in microfluidics. We invite emerging investigators and pioneers to contribute commentaries, perspectives and insightful reviews on related topics. The various insights from esteemed colleagues will be collated. We will also discuss technological breakthrough of original works in both short communications and full papers. The main idea is to stimulate the community and to provide an unique collection of insightful papers. We will also cover various topics ranging from 3D printing, paper-based microfludics to conventional polymer-based microfluidics which contributes to the technological advancements.